ANALISIS IMPLEMENTASI SANKSI PADA RUMAH MAKAN PADANG (UNIT USAHA DENGAN KONSEP MANAJEMEN SYARIAH) - ARHIPEN YAPENTRA (Universitas Islam Negeri Imam Bonjol Padang, 2018)
This study aims to explain the implementation of sanctions for employees of restaurant Padang as one form of Small and Medium Enterprises (UMKM) with a syariah management (lost and profit sharing). This research is a case study by descriptive method through structured interviews with 9 informants with varying long time of work and job/duties. From the presentation and interview with informants concluded that the implementation of sanctions for employees refers to the concept of sharia business, namely profit and lost sharing. One of the sanctions imposed for disciplinary action is to impose a fine or deduct the amount of profit sharing that is part of the employee by the terms set in such a way as to minimize the occurrence of the offense. On the other hand, the collected fines are distributed to all employees by using the ratio of